The State category in the curriculum of the School of Social Work - Fallas Jiménez, Yessenia Isabel (2022)
Introduction: The research project Historical foundations of the genesis of the modern State and its relationship with capitalist production conducted among other activities an analysis of the way in which the discussion on the State and social policy is approached in the School of Social Work from the courses State Theory and Social Policy. Objective: The first objective of the project states: "Identify the main theoretical foundations within the Marxist field that provide elements for the understanding of the modern State", derived from the study of the theoretical sources within the Marxist field, an analysis of the content and methodological aspects contained in the courses for the approach of these categories was carried out. Method: The research focuses its attention on technical elements referred to bibliographic and documentary research. For the approach of this analysis, the program of both courses was studied, identifying tendencies in the pedagogical strategy and in the theoretical perspective of the contents of both programs. Results: The predominance of a fragmentary tendency was identified in the approach to the categories State and Social policy, apprehending the historical elements as historiographic background blueprints for the analysis of the objects and not, as elements that constitute the social nature of the objects. Conclusions:Although it is possible to identify in the contents of the courses some issues referred to the historical process, the methodological aspects of the approach fragment the understanding of this process by privileging a technical and administrativist analysis of the State and social policy